Infant Feeding Practices Using Local Flours in Relation to Nutritional Status of Children Aged 6 to 24 Months Surveyed in Maternal and Child Protection Centers of Abidjan (Côte d’Ivoire) - Bamba, Mandoué Stéphanie; Gbogouri, Grodji Albarin; Agbo, Edith Adouko; Digbeu, Dogoré Yolande; Brou, Kouakou (International Journal of Child Health and Nutrition, 2018)
Objectives: The aim of the study is to evaluate the use of local flours in supplementary feeding for 6 to 24 month old children in relation to their nutritional status in Abidjan. Methods: A cross-sectional survey was conducted on 480 mother-child couples in twelve maternal and child protection centers located in four municipalities in Abidjan. Questionnaires focused on the economic characteristics of mothers, the frequency of use of local flours, sources of local flours, ingredients used for flour production. The local composite flours mainly consumed by the children were sampled for biochemical analysis. Results: Our of the 480 mothers, 73% had an income-generating activity and 27% had no activity, 10% of them were students. About 13% of the mothers with income-generating activities use only local flours, 10% of them mainly use industrial flours and 50% alternately use local flours and industrial flours. All mothers used cereals for flour production, 1% of the mothers used cassava and 98.54% used soya flour as supplement. The local flour mainly consumed, "Anango baka" with two variants, was unbalanced as far as its nutrient composition is concerned. The nutritional status of the children surveyed showed that stunting was the most widespread form of malnutrition with a prevalence of 17.9%. Conclusion: The three local composite flours used by the mothers showed a poor nutritional value. A high rate of chronic malnutrition has been reported for 6 to 24 month old children visiting maternal and child protection centers located in Abidjan.